Improving fodder yield and nutritional quality of Vigna unguiculata L. through crop establishment and nutrient management techniques - Cheenu, K; Anaytullah, S (Plant Science Today, 2025)
Cowpea, botanically known as Vigna unguiculata L., is recognized as a source of nutritious fodder due to the presence of high protein content, biomass and nitrogen-fixing ability, establishing it as a good fodder crop. To maintain its biomass growth and high quality, special attention needs to be given while selecting the best method of sowing and nutrient management to produce healthy and nutritious fodder. Keeping in view, the experiment was conducted in the factorial RBD with two factors and three replications, i.e. crop establishment methods and nutrient management during the Kharif seasons of 2023 and 2024. The crop establishment methods include raised-bed and drilling methods, while the eight possible combinations of nutrients were used as nutrient management. Results obtained from the study indicated that the raised-bed method of sowing was significantly superior (p <0.05 %) for most of the traits as compared to the drilling method. As per nutrient management is concerned, B6 i.e. a combination of nutrient with 100 % Recommended Dose of Fertilizer (RDF) + 1 spray of 0.5 % boron was recorded significantly highest value (p <0.05 %) for the plant height, dry matter accumulation, total number of leaves, total leaf area, number of primary branches, number of nodules, leaf area index and crop growth rate, green and dry fodder yield which was followed by B3 i.e. a combination of 100 % RDF + 1 spray of 1 % MgSO4. The quality parameters, such as SPAD index, crude protein, crude fiber, crude fat and ash content, were also detected significantly highest in B6 as compared to the remaining treatments. These findings reveal the integrated approach of the raised bed method in combination with 100 % RDF + 1 spray of 1 % MgSO4 can effectively enhance both green and dry fodder yield, along with the nutritional quality of cowpeas.